RANCANGAN APLIKASI BIMBINGAN BELAJAR BAHASA INGGRIS YANG DIKELOLA KELOMPOK KERJA GURU JAKARTA BARAT - Fernando Fernando; Viny Christanti M. (PROSIDING SERINA, 2021)
Kelompok Kerja Guru is an organization consisting of teachers who gather based on certain classes, fields or subjects. The Primary School English KKG is one of the KKG consisting of 120 English teachers for the elementary school level. English lessons are no longer mandatory at the elementary school level. After several years, it can be seen that there is a difference between students whose schools are still able to provide local content to English lessons. The quality of English lessons between schools is also different. In this era of globalization, of course, English is an important language in communication. Although Indonesian is still the main language, English is still needed to communicate internationally. The differences and difficulties of teachers in providing English lessons according to a standard curriculum and in accordance with the material prepared by teachers throughout Indonesia are a problem. The teacher's limited time in distance learning that is currently happening is also one of the obstacles for teachers to deliver material to students. One way to improve the quality of learning is to provide tutoring. In this pandemic, online technology remains an option in distance learning. Therefore, online tutoring is needed and a tutoring platform is needed in online learning. The tutoring application is needed in the delivery of English learning, of course, it needs to be equipped with a Chatbot so that it can help students ask questions. Chatbots are prepared in the tutoring application to help reduce the burden on teachers in answering student questions. In preparing materials for tutoring applications, teachers need to know how to create materials digitally. Increased knowledge of teachers is provided in the form of socialization and training.